Palembang Shi pada Masa Pemerintahan Militer Jepang Tahun 1942-1945 - Arma Mita (Lembaran Sejarah, 2019)
This study investigated about the Japanese military rule in the city of Palembang in 1942 to 1945, especially regarding the rule of Palembang Shi (Municipality). In this study, it will cover some of the main points of the study those are how the Japanese military rule formed the Palembang Shi rule, the structure of Palembang Shi rule and the policies that were passed during that reign. Therefore, the period of Japanese government in Indonesia it had a unique distinction that must have been different during the colonization of the earlier Dutch Indian government and its civil society. The differences in those government that was also became a distinct feature of this study which is centaintly very interesting  for us to consider and to learn more carefully. Naturally this study aims to add our insight into the history of the government development in the city of Palembang.